Rise and fall of the Berlin Wall [videorecording (DVD)] - Halmburger, Oliver; Nemrow, Clayton (A&E Television Networks : distributed in the U.S. by New Video, 2009)
Computer-generated imagery, re-enactments, archival footage, and expert commentary provide political and historical context while helping to illustrate how construction progressed over time - and how it was suddenly demolished by civilians in 1989.